Effects of Climate Smart Agricultural practices and Planting Dates on Maize Growth and Nutrient Uptake in Semi-Arid Tanzania - Gamba, A.M.; Kimaro, Anthony A.; Mtei, K.M. (International Journal of Biosciences, 2020)
The shift of growing season’s onset due to rainfall and seasonal variability are among the climate change impacts affecting agricultural productivity in semi-arid. Previous studies have also noted the seasonal variations in planting windows in semi-arid Tanzania. Because of such rainfall variability due to uncertainties of climate change, farmers face difficulties in determining the appropriate planting dates. Though, climate-smart agriculture (CSA) practices are reinforced to mitigate such climatic extremes and sustain crop production, there is limited information on the performance of CSA practices under the uncertainty of planting windows due to unpredictable rainfall on-set and patterns. This study assessed the effects of CSA practices at different planting windows on maize growth and nutrient uptakes at Mlali village of Dodoma, Tanzania. A split-plot experimental design was adopted, treatments involved CSA practices (Chololo pits, tied ridges, intercropping and Ox-cultivation – as a control) and/at planting windows (Early, Normal and Late planting). The planting windows were determined based on previous studies and Tanzania national weather forecasts. The results showed that, CSA practices had a significant (p < 0.05) effect on maize height and N nutrient uptake. Similar biomass and Mg nutrient uptake were significantly affected (p < 0.05) by both CSA practices and planting dates though Leaf Area Index (LAI) were significantly affected (p < 0.05) by planting windows. Chololo pits and tied ridges and late planting dates had the highest soil moisture, plant heights, and biomass. Ox-cultivation had a slight high N, K and Mg nutrient uptake followed with Chololo pits and tied ridges.